2006
DOI: 10.1016/j.jpainsymman.2005.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam as Adjunct Therapy to Morphine in the Alleviation of Severe Dyspnea Perception in Patients with Advanced Cancer

Abstract: The mainstay of dyspnea palliation remains altering its central perception. Morphine is the main drug and anxiolytics have a less established role. This trial assessed the role of midazolam as adjunct therapy to morphine in the alleviation of severe dyspnea perception in terminally ill cancer patients. One hundred and one patients with severe dyspnea were randomized to receive around-the-clock morphine (2.5 mg every 4 hours for opioid-naïve patients or a 25% increment over the daily dose for those receiving ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
2
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(152 citation statements)
references
References 30 publications
4
128
2
10
Order By: Relevance
“…Although small series describe relief of dyspnea with the administration of nebulized opioids [65], randomized controlled trials and a Cochrane review did not show that nebulized opioids are effective for dyspnea [66]. Benzodiazepines may be helpful in some patients when dyspnea is related to a panic disorder or severe anxiety, and corticosteroids may be effective in dyspnea re-lated to carcinomatous lymphangitis or treatment-related pneumonitis [61,67,68].…”
Section: Dyspneamentioning
confidence: 99%
“…Although small series describe relief of dyspnea with the administration of nebulized opioids [65], randomized controlled trials and a Cochrane review did not show that nebulized opioids are effective for dyspnea [66]. Benzodiazepines may be helpful in some patients when dyspnea is related to a panic disorder or severe anxiety, and corticosteroids may be effective in dyspnea re-lated to carcinomatous lymphangitis or treatment-related pneumonitis [61,67,68].…”
Section: Dyspneamentioning
confidence: 99%
“…They found that the combination of this benzodiazepine with morphine had a positive effect on dyspnea with minimal effect on somnolence. [11] In contrast to these results, Simon and et al (2010) stated that there is no evidence to support the efficacy of benzodiazepines in the palliation of dyspnea in their metaanalysis. [5,12] More randomized, controlled studies aimed at assessing the efficacy of benzodiazepines used in conjunction with other opioids need to be performed.…”
Section: Diagnosis Of Dyspneamentioning
confidence: 96%
“…There is one study which shows that morphine and midazolam give additional benefit when administered together in dyspnoeic patients in the dying phase (last hours of days of life), compared with giving midazolam alone (56). Although morphine alone gave more relief than midazolam alone, the combination was still the more efficacious option.…”
Section: Are There Agents That Synergistically Enhance the Efficacy Omentioning
confidence: 99%